Strategie rozvoje rodinného podniku - Hrachovec, Lukáš (Vysoké učení technické v Brně. Fakulta podnikatelská, 2017)
Diplomové práce pojednává o strategii rozvoje rodinného podniku Trojkámen s.r.o., který poskytuje ubytovací a restaurační služby. Na základě analýz současného stavu rodinného podniku, vnějšího prostředí, strategie a vize rodiny, navrhnu možnosti budoucího rozvoje rodinné společnosti.

Master thesis is about strategic development of family-owned company Trojkámen s.r.o, which provides accommodation and restaurant services. Based on analyses of current situation of family-owned company, outer environment, strategy and vision of family, I will suggest options for future development of the family company.
Development Strategy for Family Owned Company
Keywords: Rodinný podnik; rozvoj; strategie; strategická analýza; SWOT.; Family business; development; strategy; strategy analysis; SWOT.